Environmental factors influencing lek site selection in the red bird of paradise (Paradisaea rubra) in Raja Ampat, Southwest Papua, Indonesia - RHAMA BUDHIANA; ARIEF HAMIDI; JARWADI BUDI HERNOWO; YUDI SETIAWAN (Society for Indonesian Biodiversity, 2025)
Abstract. Budhiana R, Hamidi A, Hernowo JB, Setiawan Y. 2025. Environmental factors influencing lek site selection in the red bird of paradise (Paradisaea rubra) in Raja Ampat, Southwest Papua, Indonesia. Biodiversitas 26: 5277-5286. Understanding the ecological determinants of lek site selection is crucial for the conservation of lek-breeding species, such as the red bird-of-paradise (Paradisaea rubra), which is endemic to Waigeo and Batanta Islands in Raja Ampat, Indonesia. This study aimed to identify the primary habitat characteristics that influence lek-site preferences in P. rubra by employing a spatially explicit, multivariate methodology. Ten environmental variables (tree diameter, tree height, lek height, lek diameter, lek angle, lek length, altitude, slope, temperature, and humidity) were documented across known lek sites, and Principal Component Analysis (PCA) was employed to address collinearity and capture ecological gradients. A multiple linear regression model was then applied to the principal components to assess their association with lek suitability (Y). Three principal components were extracted: PC? (topographic openness), PC? (microclimate), and PC? (vertical structure). Regression results identified PC? as the strongest predictor of lek suitability (B: -2.629, p: 0.002). PC? represents a topographic canopy gradient, with higher values indicating denser canopy and steeper terrain at higher elevations. The negative regression coefficient, therefore, indicates that males preferentially select leks in structurally open habitats with gentler slopes, reduced canopy density, and moderate elevations. PC? and PC? had positive but non-significant effects (p>0.1), though both suggest that lek preference may also be influenced by microclimate comfort and vertical signal projection. Lek site selection in P. rubra is strongly influenced by structural and spatial habitat features, especially canopy openness and elevation. The findings emphasize that lek selection in P. rubra is shaped by the interplay of topography, microclimate, and vertical structure. Conservation strategies should prioritize protecting ridge top forest zones and limiting forest infill from secondary growth or plantation encroachment, which may disrupt lek functionality and reduce reproductive opportunities in this iconic species.